STENOGRAFI, KETERGANTUNG PADA TEKNOLOGI DAN PELESTARIAN - Sri Eka Sadriatwati (Politeknik Negeri Semarang, 2014)
For company employee, especially secretaries and journalists, ability for quick writing is essential, because quick writing can lead to quick delivery of message to addressees. Skill in quick writing (stenography) needs to be applied vocational school students, particularly for those majoring in office and administration. It is hoped that the work of Indonesian people will not get missing. Keeping Indonesian people’s work is the duty of educators and government. Feeling shy and inferior is not necessary in learning stenography writing, because those feelings may cause obstacles for beginners in understanding stenography. Patience, hard-work and thoroughness is the base in writing stenography.